Measurement of Typhim Vi IgG as a Diagnostic Tool to Determine Anti-polysaccharide Antibody Production Deficiency in Children - Guevara-Hoyer, Kissy; Gil, Celia; Parker, Antony R.; Williams, Leigh J.; Orte, Carmen; Rodriguez de la Peña, Antonia; Ochoa-Grullón, Juliana; Rodriguez De Frias, Edgard; García, Irene Serrano; García-Gómez, Sonia; Recio, M. José; Fernández-Arquero, Miguel; et al. (Frontiers in Immunology, 2019)
Background: The assessment of specific polysaccharide antibody production plays a pivotal role in the diagnosis of humoral primary immunodeficiencies (PID). The response to 23-valent pneumococcal vaccine (PPV) remains the gold standard for the diagnosis of polysaccharide antibodies. However, in Spain, the interpretation of pure polysaccharide 23-valent immunization is hampered by the high endemicity of pneumococcal disease and the generalization of the 13-valent adjuvant pneumococcal vaccination. Specific Typhim Vi (TV) IgG response to immunization is useful in adult PID, but there is no data regarding children. Objectives: To evaluate the clinical utility of TV IgG production as a diagnostic tool to determine anti-polysaccharide antibody production deficiency in children, when the response to PPV is unclear and isolated determination of serotypes is unfeasible. Methods: We conducted a single-institution prospective observational study on 61 children with recurrent infections. Baseline specific antibodies against PPV and TV were evaluated. In 28 children (46%), the response to the production of antibodies confirmed a clinical suspicion of humoral PID, and they were therefore immunized with 23-valent pneumococcal vaccine and Typhim Vi. Both specific antibody responses were measured by ELISA (The Binding Site Group Ltd, Birmingham, UK) using previously published cut-offs. Results: Seventy percent of the 61 children displayed baseline PPV >27 mg/L, whereas only 8% showed TV >28U/mL (p<0.0001). Twenty-one of 28 (75%) achieved a 3-fold increase in post-vaccination TV levels, whereas only 3% achieved a 4-fold increase in post-vaccination PPV, mainly due to high baseline PPV titers. When we classified children according to their response to TV as responders or non-responders and compared this with the well-known clinical warning signs of the Jeffrey Modell Foundation, the proportions of children with history of pneumonia and the need for intravenous antibiotics were significantly higher in TV non-responders than in TV responders (p=0.02 and p =0.01, respectively). Conclusion: Response to TV can be considered an ancillary diagnostic tool to determine polysaccharide antibodies in children, particularly when isolated determination of pneumococcal serotypes is not feasible. TV provides a useful asset for clinicians in the era of conjugate PPV vaccination, with clinical relevance. Further research is warranted for validation.